PENGARUH UMUR PANEN DAN TINGKAT MASERASI TERHADAP KANDUNGAN KURKUMIN DAN AKTIVITAS ANTIOKSIDAN EKSTRAK KUNYIT (Curcuma domestica Val.) - Julyantika Nica Dewi, Putu; Hartiati, Amna; Mulyani, Sri (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 4 No 3 (2016): September)
This study aims to determine  the effect of age harvest  and maceration levels  on curcumin content and  antioxidant  activity of turmeric extract, and determine the age of harvest and maceration on antioxidant activity.  This study use a randomized complete block design (RCBD) with two factor, the first factor consists of three ages of harvest (9, 10, and 11)  months, and the second factor consists of three levels of maceration (1, 2, and 3) times,  treatments are grouped into two based on the time of execution. The variables measured are: curcumin, the yield of the extract, the antioxidant capacity with DPPH method, and total phenolic.  The results showed that  age of harvest  did not significantly affect the curcumin content.  Age of harvest  and maceration levels significantly affect the yield of turmeric extract. Age of harvest and maceration levels also did not significantly affect to the antioxidant capacity and total phenolic of turmeric extract.  Age of harvest to produce the  highest  yield of turmeric extract is age of harvest 11 months with yield 23,63%, antioxidant capacity 6,60 (mg GAEAC / 100 g sample) and total phenolic 24,03 (mg GAE / 100 g sample). Maceration level to produce the  highest  yield of turmeric extract is  3 times maceration with yield 26,45%, antioxidant capacity 6,83 (mg GAEAC / 100 g sample) and total phenolic 23,92 (mg GAE / 100 g sample). Keywords: turmeric, age harvest, level of maceration, curcumin, antioxidant activity
Keywords: 111,